Video summarization of person of interest (POI) - Lit, Laura Pei Lin (Nanyang Technological University, 2022)
With the increase of video content available, there is a greater need for data management of these digital media. Video summarization aims to create a succinct and comprehensive synopsis through the selection of key details from video media [1]. Most video summarization models summarize the entire video without any prior trimming of key details which may lead to excess information being provided. Conventional video summarization models only provide one summarized statement for the entire video, which often results in a very broad description of activities that happened in the video.